Service Quality Determinants of Customer Satisfaction: Evidence from a Logistics Company - Ar Rozii, Rosyad Erdi; Jiwa Juwita, Himmiyatul Amanah (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The increasingly fierce competition in the logistics service industry has made service quality a crucial factor in creating competitive advantage and improving customer satisfaction. PT Karunia Indah Delapan Expres, Ngawi Branch, as one of the players in this industry, faces challenges in maintaining and increasing revenue, which is believed to be caused by low customer satisfaction with the services provided by the company. This quantitative explanatory study aims to analyze the influence of service quality on customer satisfaction using the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The data were collected through questionnaires distributed to 60 respondents and analyzed using multiple linear regression. The results show that tangibles, reliability, responsiveness, and empathy simultaneously have a significant influence on customer satisfaction, while assurance does not have a significant effect. Partially, reliability and empathy are the most dominant dimensions influencing customer satisfaction. These findings indicate that consistent service improvement and personal attention are key factors in building customer satisfaction and loyalty in the delivery service sector.